HUBUNGAN PENGETAHUAN TENTANG MITIGASI BENCANA BANJIR DENGAN SIKAP KESIAPSIAGAAN MASYARAKAT MENGHADAPI BANJIR DI RW 05 KELURAHAN GEDONG PANJANG KECAMATAN CITAMIANG KOTA SUKABUMI - Waluya, Ady; Wahyudin, Dedi (Yayasan Putra Sukamanah Sejahtera, 2024)
Knowledge of disasters is the main reason for someone to carry out existing protection activities or preparedness efforts. Disaster preparedness is a condition in which society, both individually and in groups, has the ability to anticipate the possibility of a disaster occurring in the future. Flooding is the flow of water on the ground surface that is relatively high and cannot be accommodated by channels (drainage) or rivers, so that it overflows to the right and left and causes puddles/flows in amounts that exceed normal and results in losses to humans. Disaster management is a continuous process in which the government, business world, and civil society plan and reduce the effects of disasters, take action immediately after a disaster occurs, and take steps for recovery. The type of research used in this research is correlational research . The population in this study were all heads of families in RW 5, Gedong Panjang Village, Citamiang District , Sukabumi City. The sampling method that will be used in this research is the total sampling technique. This research's bivariate analysis will use statistical tests Chi- Square. Based on statistical test results Chi Square showing p value 0.000 6 (< 0.05) which means that there is a relationship between disaster knowledge and the preparedness attitude of residents in facing flood disasters among respondents. There is a relationship between disaster knowledge and residents' preparedness attitudes in facing flood disasters. Recommended for residents of Rw 05 Kelurahan Gedong Panjang District Citamiang, Sukabumi City can face preparedness in the face of flood disasters.